Experimental Study on Positive Reinforcement Using Picture Cards to Improve Elementary School Students' Writing Skills - Anisa Farah Adiba; Awang Setiawan Wicaksono (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
Writing is a fundamental literacy skill that remains a major challenge for elementary school students in Indonesia. Many students experience difficulties in organizing ideas, constructing sentences, and maintaining writing motivation, which negatively affects their literacy development. This study aimed to examine the effectiveness of positive reinforcement using picture card in improving elementary school students’ writing skills. The research employed a experimen approach with a One Group Pretest–Posttest Design. The participants were 20 third-grade students from UPT SDN 26 Gresik, selected based on initial screening results. Data were collected using a validated writing skill assessment covering aspects of letter formation, sentence construction, spelling accuracy, and writing neatness, and were analyzed using the Wilcoxon Signed Rank Test. The results indicated a significant improvement in students’ writing performance, with the mean score increasing from 25.00 in the pretest to 36.50 in the posttest, representing a 57% improvement. Statistical analysis showed a significant difference between pretest and posttest scores p = 0.001 (p < 0.05), with all participants demonstrating positive score gains. These findings confirm that positive reinforcement supported by picture card media is effective in enhancing elementary students’ writing skills. The study strengthens the application of Skinner’s operant conditioning theory in literacy learning and offers practical implications for developing engaging, motivating, and student-centered writing instruction in elementary education.